Vitreous Humor: Composition, Characteristics and Implication on Intravitreal Drug Delivery - Mishra, Deepakkumar; Gade, Shilpkala; Glover, Katie; Sheshala, Ravi; Singh, Thakur Raghu Raj (Current eye research, 2023)
Purpose: Intravitreal administration of drug molecules is one of the most common routes for treating posterior segment eye diseases. However, the properties of vitreous humour changes with the time. A number of ocular complications such as liquefaction of the vitreous humour, solidification of the vitreous humour in the central vitreous cavity and detachment of the limiting membrane due to the shrinking of vitreous humour are some of the factors that can drastically affect the efficacy of therapeutics delivered via intravitreal route. Although significant research has been conducted for studying the properties of vitreous humour and its changes during the ageing process, there have been limited work to understand the effect of these changes on therapeutic efficacy of intravitreal drug delivery systems. Therefore, in this review we discussed both the coomposition and characteristics of the vitreous humour, and their subsequent influence on intravitreal drug delivery. Methods: Articles were searched on Scopus, PubMed and Web of Science up to March 2022. Results: In this review, we discussed the biological composition and biomechanical properties of vitreous humour, methods to study the properties of vitreous humour and the changes in these properties and their relevance in ocular drug delivery field, with the aim to provide a useful insight into these aspects which can aid the process of development of novel intravitreal drug delivery systems. Conclusions: The composition and characteristics of the vitreous humour, and how these change during natural aging processes, directly influence intravitreal drug delivery. This review therefore highlights the importance of understanding the properties of the vitreous and identifies the need to achieve greater understanding of how changing properties of the vitreous affect the therapeutic efficacy of drugs administered for the treatment of posterior eye diseases.